Leadership : Junior Commanders - Attiqur Rahman, Mohammed Lt. Gen. (Lahore Ferozsons Ltd., 1973)
The Book is written within the framework of the infantry but will also help also officers. Indeed its theme would be useful to all those who have men to command, supervise and look after whether in the army or outside.
Keywords: Pakistan. Army -- Leadership